2015
DOI: 10.1097/opx.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simulated Hyperopia on Academic-Related Performance in Children

Abstract: A relatively low level of simulated bilateral hyperopia impaired children's performance on a range of academic-related outcome measures, with sustained near work further exacerbating this effect. Further investigations are required to determine the impact of correcting low levels of hyperopia on academic performance in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…9 However, preliminary evidence that normalization of deficits may be possible with spectacle correction 17 and the report of reduced reading and academic performance with simulated hyperopia 29 seem to argue against the theory that a irremediable neural deficit underlies the performance differences. Furthermore, the association between hyperopia and deficits in visual, but not auditory aspects of early literacy found in this study and the study by Shankar et al 18 argue against this theory.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, preliminary evidence that normalization of deficits may be possible with spectacle correction 17 and the report of reduced reading and academic performance with simulated hyperopia 29 seem to argue against the theory that a irremediable neural deficit underlies the performance differences. Furthermore, the association between hyperopia and deficits in visual, but not auditory aspects of early literacy found in this study and the study by Shankar et al 18 argue against this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Shankar et al (2007) have reported uncorrected hyperopia (>2.00DS) in children aged 4 to 7 years with reduced performance in letter and word recognition, receptive vocabulary and emergent orthography [16]. In simulated refractive error studies, children with low levels of bilateral hyperopia (+2.50DS) and bilateral astigmatism (1.50 DC) doing sustained near work (20 minutes) had reduced performance in academic-related measures (reading, visual information processing and reading related eye movement tests) [17, 18]. Early identification and correction of refractive error can avoid its effect on learning and academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…20 Reported deficits in visuocognitive and visuomotor ability in hyperopic children have been attributed to a neural processing deficit in hyperopia. 9 However, preliminary evidence that normalization of deficits may be possible with spectacle correction 17 and the report of reduced reading and academic performance with simulated hyperopia 29 seem to argue against the theory that a irremediable neural deficit underlies the performance differences. Furthermore, the association between hyperopia and deficits in visual, but not auditory aspects of early literacy found in this study and the study by Shankar et al 18 argue against this theory.…”
Section: Discussionmentioning
confidence: 99%